Exploration Of Parenting Practices In The Na'apu Liana, Nahoni Liana And Napoitan Liana Traditions Of The Boti Tribe - Afi, Ayu Patrisia; Bali, Engelbertu Nggalu; Margiani, Kristin; Seran , Theodorina Novyani; Koten, Engelikus Nama; Betty, Credo G. (Exploration in Early Childhood Research, 2024)
Childcare practices in the na'apu liana, nahoni liana, and napoitan liana traditions carried out by the Boti tribe community are ancestral heritage that is maintained to this day. This study aims to explore and describe childcare practices in the na'apu liana, nahoni liana, and napoitan liana traditions in the Boti tribe community. Qualitative research method using data collection techniques in-depth interviews with 15 people (1 Boti chief, 1 traditional leader, 2 community leaders, 2 educational leaders, and 9 parents) and participatory observation for 1 month. The results showed that childcare practices in the Boti tribe are closely related to cultural values and traditions that are rich in values and traditions. The na'apu liana tradition is a tradition carried out when pregnant women, the Boti people believe that the rituals performed in this tradition can provide special care for pregnant women with a focus on health, and spiritual preparation to welcome the presence of the baby. The nahoni liana tradition is a tradition carried out when the mother is in labor, emphasizing emotional, spiritual, and physical support to the mother and baby. Meanwhile, the napoitan liana tradition is a tradition carried out at the post-birth stage, this ritual is carried out to introduce the baby to the Boti community about the baby's presence. These findings illustrate the complexity and depth of the parenting system in Boti culture that reflects the harmony between tradition, the environment and the needs of child development.